Content Distribution Analysis on Gibran Rakabuming Raka’s SGIE Questions in Indonesia’s 2024 Election Debate - Almira Kusumowardani Habsari; Alfa Pandutama; Muhammad Alviansyah Hidayat (Green Publisher Indonesia, 2024)
The 2024 general election in Indonesia has seen a significant increase in social media usage, especially in response to the candidates' debates. In this study, Gibran Rakabuming as one of Indonesia's vice-presidential candidates became a hot issue in asking the State of the Global Islamic Economy (SGIE) question at the debate which became an important indicator of public interest and sentiment. This research uses content distribution theory analysis to understand the implications of social media use on political campaigns and how political content is disseminated and responded to by other social media users. The results of this study show that the use of social media in response to SGIE responses strengthens positions and relationships with voters.